The consideration of video-based technique in foreign language for speaking skill divelopment : psycholinguistic review case study second year LAmmar Thelidji University of Laghouat Faculty of Letters and Langues Department of EnglishMD - Guedim ,Nour El Houda; Marfoua Karima; Belhadj ,Abd El Krim (Faculty of Letters and Foreign Languages Department of English, 2017)
This research shed light on a technique and a useful tool in the field of teaching and learning foreign languages called video-based technique. Many teachers have considered it as a beneficial aid in teaching ESL/EFL. This work aims to seek the effectiveness of video-based technique on the learners’ speaking skill and communicative competencies development. The current research study focuses on conducting the use of the video-based technique on maximizing the learners’ oral skills. The work highlights the importance of using this technique with students of foreign languages. The main hypothesis adopted in this research study is that the effective use of the video-based technique can greatly help both the teachers to engage in professional development and the students to improve their oral communication skill. Also, this research aims to focus on the various kinds of video-based technique, and prove that their application can stimulate and motivate the student to develop his/her learning skills. This work is based on second year LMD students’ questionnaire aiming to know more about the effectiveness of using the video-based technique in developing the learners speaking skill development. Through the analysis and the data collected, we noticed that the students consider the video-based technique as an essential technique in stimulating their oral communication skill, in addition to this; it increases highly their motivation and creates a real world communication for them